The Role of R&D in Oligopoly Competition: Are Companies in Oligopoly Markets More Innovative? - Judijanto, Loso; Wulandjani, Harimurti (West Science Business and Management, 2025)
This study investigates the role of Research and Development (R&D) in fostering innovation within oligopolistic markets, addressing whether firms in these markets are more innovative compared to those in other market structures. Employing a systematic literature review approach, 15 Scopus-indexed publications were analyzed to synthesize insights on R&D intensity, innovation strategies, and the influence of regulatory environments in oligopolies. The findings reveal that firms in oligopolistic markets exhibit higher R&D intensity due to their resource capabilities and competitive dynamics. Innovation is driven by rivalry, collaborative strategies, and supportive regulatory frameworks. However, excessive market concentration can dampen innovation by reducing competitive pressures. Industry-specific trends further highlight variations in innovation outcomes, with high-tech sectors demonstrating higher R&D activity. These results have implications for policymakers and business leaders, emphasizing the need for balanced regulatory policies and strategic R&D investments to maximize innovation outcomes in oligopolistic markets.